Effects of Selected Plant Growth Regulators on Regeneration of Mangosteen (Garcinia Mangostana L.) Using Tissue Culture Technique - Sirchi, Mohammad Hossein Torabi (2009)
The in-vitro plantlet regeneration system via organogenesis and callus induction was developed from various mangosteen explants (seed, shoot tip, stem and leaf) using various plant growth regulators (PGR). For shoot induction, the mangosteen half seed, leaf and stem explants sufficiently achieved shoot regeneration rates above 60% of total explants cultured (70%, 60% and 60% respectively) on various auxin and cytokinin supplementation into the basal MS medium [4.0 mgL-1 (w/v) BAP with 0.2 mgL-l (w/v) NAA for seed; 1.0 mgL-l (w/v) BAP in combination with 0.05 mgL-1 (w/v) KIN for stem; 2.0 mgL-l (w/v) of BAP for leaf]. Shoot induction from the shoot tip explant was not successful. However, among the three explants, the leaf explant gave the highest mean number of s hoots at 46.5 ( seed and stem at 9.3 and 8 . 9 respectively). Mean shoot height h ow ever, was 0.48 em for leaf, while it was h igher for shoots generated from stem and seed explants (0.7 em and 0.8 em respectively). The shoots rooted successfully o n ful l strength M S medium w ithout IBA w i th high percentage of root formation (87%) and number of roots ( 3 . 8 ) (seven months after culture). The p l an tlets were then successfully potted and acclimatized o n medium containing soil + sand+ organic matter+ vermiculite m i x ture (2:2: 1: 1) which gave the h ighest n umber of l eaves (6.5), plant height (3.5cm) and percentage of plant survival ( 8 0%). As for callus induction, i nduction from seed and leaves w as 90% on medium with 0.5 mgL-' (w/v) NAA, whi le i nduction from shoot tip and stem was 90% and 83% respectively on medium with 0.2 mgL-' ( w/v) KIN. Our study has successfully developed a plant regeneration s ystem from e asil y avai lable stem and green juvenile leaf explants, as compared to the seasonall y available and limited seed and you n g leaf expl ants that are generall y reported by other researches. Furthermore, callus induction was successfu l from various mangosteen explants for future uti lization in the development of a plant regeneration protocol from callus, as callus also has the potential of producing improved varieties via various genetic modification techniques today.